The Role of Insulin Resistance in the Development of Hypertension: A Case-Control Study - Hasan, Rusul Hanoon; Qasim, Qutaiba A.; Al Khafaji , Adnan Taan (American Journal of Biomedicine and Pharmacy, 2025)
Hypertension represents a significant global health challenge, impacting approximately 1.28 billion adults globally. It is a major risk factor for cardiovascular illnesses, stroke, and renal failure, leading to considerable morbidity and mortality. Despite extensive knowledge and advancements in therapy, the exact mechanisms behind hypertension remain incompletely elucidated, especially concerning the roles of metabolic and inflammatory processes. This study comprises a case-control design involving 150 participants: 100 patients and 50 healthy controls. The research was conducted from October 2023 to July 2024. Patients with hypertension were selected from AL Nasiriyah Teaching Hospital. The age, gender, family history, smoking status, social activity, and food habits of each individual were documented. The history of diseases, certain social activities, HbA1c levels, random blood sugar measurements, and other sociodemographic variables of the patients were collected using a reported technique (questionnaire). Individuals afflicted with hypertension and chronic illnesses. The mean red blood cell count in the patient group was (87.9980±17.83), compared to (68.3716±13.71) in the control group, with a P value <0.05. Conversely, the mean cumulative sugar test did not differ between the groups, with the patient group at (5.0148±0.43) and the control group at (5.0498±0.22), yielding a P value >0.05. In contrast, insulin and HOMA-IR tests demonstrated elevated levels (7.5478±4.41 and 1.1380±0.73, respectively) as compared to the control group (5.9392±3.81 and 0.6351±0.46, respectively), with a P value of <0.05. Elevated insulin resistance and glucose levels may be regarded as potential factors contributing to hypertension. The initiation of insulin treatment resulted in a considerable increase in both systolic and diastolic blood pressure among the patient group.